Preventing protein-dependent biofilm formation in Staphylococcus aureus by targeting the serine aspartate repeat protein C and fibronectin binding proteins - Hays, Leanne (Trinity College (Dublin, Ireland). Department of Microbiology, 2017)
Staphylococcus aureus is a leading cause of biofilm infections on indwelling medical devices. S. aureus biofilm infections are intrinsically difficult to treat. They are recalcitrant to conventional antibiotics and resistant to host immune phagocytosis. Thus, treatment often involves removal of the device and new preventive and treatment strategies are greatly required S. aureus biofilm formation is multifactorial and considered to occur through three distinct phases; primary attachment, accumulation and maturation and biofilm dispersal. Several cell wall-anchored proteins of S. aureus mediate biofilm accumulation. Proteins on adjacent cells form homophilic interactions causing cells to aggregate and biofilm to accumulate. These include the serine aspartate repeat protein C (SdrC) and the fibronectin binding proteins (FnBP) A and B. FnBPs also mediate S. aureus adherence to the host plasma protein fibrinogen (Fg) which is important for primary attachment of S. aureus to biotic surfaces. However, FnBP-mediated biofilm accumulation and adherence to Fg are mediated by two distinct mechanisms. This study investigated SdrC and FnBPs as novel targets for anti-biofilm agents in order to prevent S. aureus biofilm formation.
Embargo End Date: 2021-03-01
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin, 2017